IN VIVO TESTING OF ANTIPYRETIC LEAVES OF FENCE (JATROPHA CURCAS L) ORIGIN GORONTALO - Widy Susanti Abdulkadir; Juliyanty Akuba; Endah Nurrohwinta Djuwarno; Dizky Ramadani Papeo; Arief Ibnu Haryanto (UNG, 2023)
Jatropha (Jatropha Curcas L) is a plant that has been used empirically as a fever reducer. Fever is one of the symptoms of the disease which is characterized by a significant increase in body temperature. The novelty of this study was due to the effectiveness of Jatropha Curca L. leaf extract as an antipyretic. The purpose of this study was to determine the dose of antipyretic effectiveness of Jatropha Curcas (Jatropha Curcas L) Leaf Extract in Male Mice (Mus Musculus). Extraction by maceration using 96% ethanol solvent. 15 male mice (Mus Musculus) were divided into 5 groups, namely negative control (Na-cmc 1%), positive control (Paracetamol), and the treatment group given Jatropha leaf extract with doses of 150, 200, 250 mg/kgBW. Peptone 10% 1 ml orally as a fever inducer. And observed at 30, 60, 90 and 120 minutes after treatment. The data obtained were analyzed using one-way ANNOVA followed by the LSD test to determine differences between groups. The results showed that the leaf extract of Jatropha Curcas (Jatropha Curcas L) had an antipyretic effect where the most effective dose was at a dose of 250 mg/kgBW because it has a very stable temperature reducing power and effectiveness is comparable to Paracetamol. The conclusion of this study is that Jatropha Curcas L extract at a dose of 250 mg/kg can be used as an antipyretic.